Response to Central Boost Radiation Therapy in Unresectable Retroperitoneal Sarcoma: A Case Series - Danielle N. Burner, BS; Peter G. Hendrickson, MD, PhD; Diana M. Cardona, MD; Dan G. Blazer, III, MD; James B. Mullins, CMD; David G. Kirsch, MD, PhD (Advances in Radiation Oncology)
Purpose: Optimal treatment of retroperitoneal sarcoma (RPS) remains undefined. Here, we report the feasibility of using high-dose boost radiation (3-4 Gy) to the central part of the tumor in patients with unresectable RPS. Methods and Materials: Five patients with unresectable RPS were treated with radiation therapy using a central boost technique with intensity modulated radiation therapy. On average, doses of 25 Gy to 45 Gy were delivered to the outer part of the tumor (planning target volume 1), while the central part of the tumor (planning target volume 2) received a 56 Gy to 75 Gy physical dose, which translates to a 62.67 Gy to 87.5 Gy equivalent dose in 2 Gy fractions (EQD2). To minimize radiation toxicity to the adjacent bowel and other organs, we used sequential, interdigitated, or simultaneous integrated boost (SIB) techniques. Results: In this case series of variable RPS histology, the median survival postradiation therapy was 30 months. Three of the 5 patients had clinically stable local disease on follow-up scans, and none of the patients experienced clinically significant toxicity. Conclusions: In summary, in this small case series of 5 patients, treatment was tolerated well, and excellent local responses were observed regardless of the timing of the central boost. Given the high rates of metastatic disease that developed in responding patients, effective systemic therapy will likely be needed for unresectable RPS treated with aggressive radiation therapy to the central part of the tumor.